Elucidation of the Effects of Bisphenol A and Structural Analogs on Germ and Steroidogenic Cells Using Single Cell High-Content Imaging. (27th January 2021) - Rajkumar, Abishankari; Luu, Trang; Beal, Marc A; Barton-Maclaren, Tara S; Robaire, Bernard; Hales, Barbara F
Abstract: Concerns about the potential adverse effects of bisphenol A (BPA) have led to an increase in the use of replacements, yet the toxicity data for several of these chemicals are limited. Using high-content imaging, we compared the effects of BPA, BPAF, BPF, BPS, BPM, and BPTMC in germ (C18-4 spermatogonial) and steroidogenic (MA-10 Leydig and KGN granulosa) cell lines. Effects on cell viability and phenotypic markers were analyzed to determine benchmark concentrations (BMCs) and estimate administered equivalent doses (AEDs). In all 3 cell lines, BPA was one of the least cytotoxic bisphenol compounds tested, whereas BPM and BPTMC were the most cytotoxic. Interestingly, BPF and BPS were cytotoxic only in MA-10 cells. Effects on phenotypic parameters, including mitochondria, lysosomes, lipid droplets, and oxidative stress, were both bisphenol- and cell-line specific. BPA exposure affected mitochondria (BMC: 1.2 μM; AED: 0.09 mg/kg/day) in C18-4 cells. Lysosome numbers were increased in MA-10 cells exposed to BPA or BPAF but decreased in KGN cells exposed to BPAF or BPM. Lipid droplets were decreased in C18-4 cells exposed to BPF and in MA-10 cells exposed to BPTMC but increased in BPF, BPM, and BPTMC-exposed KGN cells. BPA and BPM exposure induced oxidative stress in MA-10 and KGN cells, respectively. In summary, structurally similar bisphenols displayed clear cell-line-specific differences in BMC and AED values for effects on cell viability and phenotypic endpoints. This approach, together with additional data on human exposure, may aid in the selection and prioritization of responsible replacements for BPA.